Spying and imperfect commitment in first-price auctions: a case of tacit collusion - Cuihong Fan; Byoung Heon Jun; Elmar G. Wolfstetter (Economic Theory Bulletin, 2023)
We analyze Stackelberg leadership in a first-price auction. Leadership is induced by an information system, represented by a spy, that leaks one bidder's bid before others choose their bids. However, the leader may secretly revise his bid with some probability; therefore, the leaked bid is only an imperfect signal. Whereas leadership with perfect commitment exclusively benefits the follower, imperfect commitment yields a collusive outcome, even if the likelihood that the leader may revise his bid is arbitrarily small. This collusive impact shows up in all equilibria and is strongest in the unique pooling equilibrium which is also payoff dominant.
Keywords: L12; L13; L41; D43; D44; D82; 330; Auctions; Tacit collusion; Espionage; Second-mover advantage; Signaling; Incomplete information